Smart Home Implementation with Home Assistant Platform in Modern Housing - Alan Tri Arbani Hidayat; M. Udin Harun Al Rasyid; Isbat Uzzin Nadhori; Yeremia Ega Wahyudi; Yoga Prastyo Bayu Laksono (ISAS, 2026)
The implementation of smart home systems using the Home Assistant platform in modern residential environment addresses residents’ needs for practical, effective, and energy-efficient home management. Although the smart home market is projected to grow by 16.3 until 2027, its adoption in Indonesia still faces challenges related to public understanding and device integration complexity. The developed system integrates temperature and humidity sensors, energy consumption measurement sensors, motion defection sensors, relays for device control, and an esp32 as the central control unit. Data from esp32 is transmitted in real-time to Firebase Real Time Database, then integrated with Home Assistant and Node-RED and add-ons for securing monitoring. Evaluation demonstrates effective performance in integrating devices from various vendors and protocols, as well as responsiveness of automation features. This development provides an efficient, cost-effective, and ease-adopted smart home implementation model, demonstrating how the open-source Home Assistant platform can enhance energy efficiency, comfort, and security for residents of modern housing in Indonesia.